Fate or Free Will? The Reception of Greek Religion in Jean Cocteau’s La Machine Infernale (1934) - Elisabeth Kruse (Religions, 2025)
In the present article we propose to analyse the link between Greek religion and philosophical concepts of the human condition as a problem of reconciling determinism and at the same time free will, with its existential and moral implications. This issue has remained a matter of revision and discussion throughout the ages and latitudes within philosophy, but also in the literature, where through myths, these questions reappear, although in very different historical and religious contexts. We propose to approach these themes through the myth of Oedipus, immortalised by Sophocles in his tragedy Oedipus Rex, which Jean Cocteau, in the tragic interwar period, rereads and resemanticises, but without losing the essential question of whether there is an insurmountable destiny that imposes itself on free will.